Probabilistic Estimation of Geothermal Reserves in Dieng Field with JIWA Power Density and JIWA Volumetric - Sholikhuddin, Mukhammad; Fahri, Dzakhi; Sihotang, Novanto; Wardana, Raka Sudira (Journal of Petroleum and Geothermal Technology, 2025)
Geothermal energy is a renewable energy source that is environmentally friendly and can be utilized for power generation. This study aims to estimate geothermal reserves in Dieng Field using Monte Carlo simulation to overcome uncertainty in the calculation of geothermal resources. The methods used include the Power Density and Volumetric Stored Heat approaches by considering geophysical, geological, and well logging data. Monte Carlo simulation produces probabilistic estimates categorized into P10, P50, and P90 scenarios. The results show that the potential geothermal reserves in Dieng Field range from 56.91 MW (P10) to 113.41 MW (P90) based on the Volumetric method and between 64.22 MW (P10) to 111.22 MW (P90) based on the Power Density method. These results provide a comprehensive picture of the geothermal potential that can be utilized, and support decision-making in the sustainable development of geothermal energy.